OIL SORBENTS MANUFACTURING FROM PLANT MATERIAL FOR WATER RESERVOIRS ECOLOGICAL IMPROVEMENT - Pavliukh, Lesya (Proceedings of National Aviation University (archive), 2013)
Methods of oil sorbents manufacturing from raw plant material are analyzed. Impact of thermal and chemical treatment on oil sorption of sawdust is presented.